Análise energética na avicultura de corte: estudo de viabilidade econômica para um sistema de geração de energia elétrica eólico-fotovoltaico conectado a rede - Nascimento, Luis Antonio Brum do (2011)
This dissertation presents a study on the feasibility economic analysis in partial or total supply of electricity from the use of photovoltaic and wind turbine generators connected to the grid supplying the loads partially or fully installed in an aviary Dark House located in the southwestern region of Paraná. The work comprises an energy analysis of avian data collected from the load curve and the profile of effective generation of wind energy conversion devices, photovoltaic spectrum under the influence of wind and solar radiation site. Simulates the energy balance between the decentralized generation of electricity to solar and wind sources connected in parallel to the conventional grid and supply all or part of the charges along with the likely surplus stored on the network using the computer program HOMER – Hybrid Optimization Model for Electric Renewable. Economic analysis for investments were made from the simulated data and projected scenarios. In the data collection phase of energy consumption goes through the records of bills of electricity, the operational programs of light and ventilation minimum suggested by the integrator and interviews with the integrated. Identifies a final consumption of electricity of 10,891 kWh / year with peaks in demand throughout the year up to 8.0 kW. Analyze the components configured by generating more efficient unit effective during the year per kW installed. Considers the historical data for wind speed and solar radiation obtained from the local government and some universities. Bring the data synthesized from renewable resources for an hourly time basis throughout the year. Complemented by a process of economic analysis, the paper verifies the feasibility of the proposed settings while under the influence of some scenarios special rates for surplus energy injected into the grid and subsidies for the purchase of photovoltaic and wind turbines. The study presents a situation as a result of the feasibility of using these energy conversion devices connected to the grid in aviaries Dark House are some desirable technical and economic scenarios are provided by the Brazilian electric power to renewable wind and photovoltaic.